Triassic foraminifers of the Lampang Group (Northern Thailand) - Kobayashi F. (2014)
Triassic foraminifers are recognized, for the first time, in limestones from four localities of the Lampang Group (Northern Thailand), tectonically assigned to the Sukhothai Subterrane (Sukhothai Folded Belt) which is located between western the Sibumasu (Shan-Thai) Terrane and eastern Indochina. Four foraminiferal associations are distinguished: (1) Glomospirella lampangensis, n. sp., (2) Pilammina densa, (3) endothyroid foraminifers-Diplotremina astrofimbriata, and (4) Aulotortus sinuosus microfaunas. Based on comparison with the coeval European faunas, they are thought to be (1) Early Triassic (?), (2) Anisian, (3) Ladinian (?), and (4) Carnian in age. Important taxa of these associations are common to those of South China and Southeast Asia. Most of them are closely similar to those of Europe, and show a remarkable contrast with those of Middle and Late Permian foraminiferal assemblages having many provincial and endemic characters. Glomospirella lampangensis, n. sp. is herein systematically described among the distinguished 41 species. © 2005 Elsevier Ltd. All rights reserved.